1993
DOI: 10.1128/jb.175.14.4538-4544.1993
|View full text |Cite
|
Sign up to set email alerts
|

Myxococcus xanthus encodes an ATP-dependent protease which is required for developmental gene transcription and intercellular signaling

Abstract: The bsgA gene of Myxococcus xanthus plays an essential role in the regulation of early gene expression during fruiting body formation and sporulation. bsgA mutants behave as though unable to initiate a required cell-cell interaction and consequently fail to transcribe normal levels of many developmentally induced genes. We determined the nucleotide sequence of bsgA, which predicts a single gene encoding a 90.4-kDa protein. The deduced BsgA protein shares 45 and 48% amino acid identity with the lon genes of Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
68
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 21 publications
1
68
0
Order By: Relevance
“…The protein encoded by bsg is homologous to the bacterial Lon protease and is essential for expression of early developmental genes (39,40). Of particular interest is the role of poly P in the activation of Lon when an E. coli culture is switched from a rich medium to a minimal medium (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by bsg is homologous to the bacterial Lon protease and is essential for expression of early developmental genes (39,40). Of particular interest is the role of poly P in the activation of Lon when an E. coli culture is switched from a rich medium to a minimal medium (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of yeast strain lacking Lon is the presence of large deletions within the mtDNA (22,27), suggesting that Lon is required for the stability and expression of the mitochondrial genome. Moreover, in vivo studies in bacteria and yeast suggest that Lon is involved in controlling gene expression, either by regulating the levels of transcription factors or by influencing the stability of mRNA transcripts (28,29). Recently, Liu et al (30) reported that ATP inhibits the binding of human Lon to DNA or RNA.…”
mentioning
confidence: 99%
“…In vivo, E. coli Lon protease specifically degrades several short-lived proteins, including the cell division inhibitor SulA and a transcriptional regulator, RcsA (7). Lon homologs have been identified in both Gramnegative and Gram-positive bacteria; in Myxococcus, one Lon-like protein has a role in development of fruiting bodies (8)(9)(10)(11). E. coli also possesses a second ATP-dependent protease, Clp, which is a multicomponent protease that degrades a variety of specific proteins as well as abnormal proteins (1, 12, 13).…”
mentioning
confidence: 99%